Analisis Kepastian Hukum Penyusunan Daftar Pemilihan Tetap dalam Menjamin Hak Pilih Konstitusional Warga Negara pada Pemilihan Umum di Indonesia - Gusti Ayu Komang Danu Antari; Ratna Artha Windari; Si Ngurah Ardhya; Ni Ketut Sari Adnyani; I Nyoman Budiada (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study aims to analyze legal certainty in the preparation of the Permanent Voter List (Daftar Pemilih Tetap/DPT) as an instrument to guarantee the constitutional voting rights of citizens in general elections in Indonesia. This research employs a normative legal method using statutory and conceptual approaches. The findings indicate that legal certainty in the preparation of the DPT plays a crucial role in ensuring the fulfillment of citizens' voting rights. An accurate, up-to-date, and legally compliant voter list minimizes the potential violation of voting rights while improving the quality of democratic, transparent, and credible elections. Therefore, stronger institutional coordination and continuous voter data updating are essential to ensure the protection of citizens' constitutional voting rights.